A comparative study of rental value of residential properties at border communities of Lagos and Ogun States, Nigeria. Issue 1 (March 2021) - Oloke, O.C.; Ezema, I.; Fayomi, O.S.I.; Emetere, M.; Omeje, M.; Jesusegun, D.
Abstract: This study delves into the pattern and level of development of two adjacent border communities of Lagos and Ogun States, Nigeria to compare the effect on rental values of residential properties in the two communities. The study attempted to find out if there are significant differences as well as definite relationship between the values. Questionnaires were distributed to two groups of respondents which are 84 estate surveying and valuation firms in Ikeja, Lagos and 152 residential property owners/residents in the two communities. Data were analysed with statistical tools such as tables, percentages and mean. Student's t-test statistics was used to ascertain the difference in rental values while Pearson coefficient of correlation was used to establish the degree of relationship. The importance of factors influencing rental values was determined using the relative importance index. Analysis were presented in percentages, tables and charts and then discussed. Result showed that there are significant statistical differences in rents of the two communities despite the proximity. It was further observed that neighbourhood density and level of infrastructure development play vital roles in the gaps observed in rental values. However, the Pearson correlation coefficient revealed that there is a relatively strong positive correlation between rental values of properties in the two communities. The research therefore concluded that for property market on the Ado-Odo/Ota side of the emerging Lagos megacity to attain its full potential, there is the need for major urban renewal, investment in physical and economic infrastructure via partnership with private sectors and property owner in the communities.